A Comprehensive Investigation of Comorbidities, Mechanisms, Injury Patterns, and Outcomes in Geriatric Blunt Trauma Patients. Issue 11 (November 2016) - Brown, Carlos V. R.; Rix, Kevin; Klein, Amanda L.; Ford, Brent; Teixeira, Pedro G. R.; Aydelotte, Jayson; Coopwood, Ben; Ali, Sadia
The geriatric population is growing and trauma providers are often tasked with caring for injuries in the elderly. There is limited information regarding injury patterns in geriatric trauma patients stratified by mechanism of injury. This study intends to investigate the comorbidities, mechanisms, injury patterns, and outcomes in geriatric blunt trauma patients. A retrospective study of the 2012 National Trauma Databank was performed. Adult blunt trauma patients were identified; geriatric (>/=65) patients were compared with younger (<65) patients regarding admission demographics and vital signs, mechanism and severity of injury, and comorbidities. The primary outcome was injuries sustained and secondary outcomes included mortality, length of stay in the intensive care unit and hospital, and ventilator days. There were 589, 830 blunt trauma patients who met the inclusion criteria, including 183, 209 (31%) geriatric and 406, 621 (69%) nongeriatric patients. Falls were more common in geriatric patients (79 vs 29%, P < 0.0001). Geriatric patients less often had an Injury Severity Score >/=16 (18 vs 20%, P < 0.0001) but more often a head Abbreviated Injury Scale >/=3 (24 vs 18%, P < 0.0001) and lower extremity Abbreviated Injury Scale >/=3 (24% vs 8%, P < 0.0001). After logistic regression older age was an independent risk factor for mortality for the overall population and across all mechanisms. Falls are the most common mechanism for geriatric trauma patients. Geriatric patients overall present with a lower Injury Severity Score, but more often sustain severe injuries to the head and lower extremities. Injury patterns vary significantly between older and younger patients when stratified by mechanism. Mortality is significantly higher for geriatric trauma patients and older age is independently associated with mortality across all mechanisms.